Diabetic foot self-care practices and its predictors among diabetes mellitus patients in Ethiopia: systematic review and meta-analysis - Sefineh Fenta Feleke; Zelalem Dejazmach; Abebe Merchaw Faris; Tesfaye Engidaw Habtie; Adugnaw Atnafu Atalay; Natnael Amare Tesfa; Getachew Derbew (BMJ Open)
Objective The study aims to identify self-care practices related to diabetic foot care and determine their predictors among diabetes mellitus (DM) patients in Ethiopia.Design Systematic review and meta-analysis.Data sources Data were collected from PubMed/MEDLINE, ScienceDirect, Google Scholar and grey literature sources. Databases were searched from inception to August 2024.Eligibility criteria Observational studies (including cross-sectional, case–control, cohort and survey designs) reporting diabetic foot self-care practices and their predictors among DM patients in Ethiopia. Our inclusion criteria encompassed articles published in English, and we considered studies conducted in both healthcare institutions and community settings.Data extraction and synthesis Microsoft Excel was used for data extraction and summary, while the analysis was performed with R software V.4.3.2. The overall pooled prevalence of diabetic foot self-care practices and their predictors were estimated using a random-effects model. Publication bias was assessed both graphically, using funnel plots, and statistically, with tests such as Egger’s regression test. The reviewers systematically assessed potential bias in individual studies using the Newcastle–Ottawa Quality Assessment Scale, and the certainty of evidence was assessed by Grade of Recommendations Assessment, Development and Evaluation (GRADE). Subgroup analysis was carried out to minimise random variations in the estimates from the primary studies.Results The pooled prevalence of good diabetic foot self-care practice in Ethiopia was 51% (95% CI: 41% to 61%; I²=98%, p≤0.001). Factors associated with diabetic foot self-care practices among diabetic patients included knowledge of foot care (adjusted OR (AOR)=2.42; 95% CI: 1.20, 3.62), being female (AOR=1.23; 95% CI: 1.02, 1.98) and rural residency (AOR=1.23; 95% CI: 1.02, 1.98). Both Egger’s test (p=0.4430) and Begg’s test (p=0.501) indicated no significant evidence of publication bias. Regarding the certainty of evidence, the overall GRADE rating is categorised as low.Conclusions The overall prevalence of good diabetic foot self-care practices among DM patients in Ethiopia is relatively high. Residence, sex and knowledge of foot care were identified as key predictors of effective foot self-care practices in this population. To enhance diabetic foot self-care in Ethiopia, it is crucial to strengthen education on foot care. Tailored interventions should be developed specifically for men and rural residents to improve their diabetic foot self-care practices.